Recent developments of strontium titanate for photocatalytic water splitting application - Phoon, Bao Lee; Lai, Chin Wei; Juan, Joon Ching; Show, Pau Loke; Pan, Guan Ting (Elsevier, 2019)
The high efficiency of SrTiO3 in the reaction of heterogeneous photocatalysis needs a suitable architecture that maximises photon absorption and minimises electron loss during excitation state. In order to further enhance the migration of charge carriers during excitation state, considerable effort has to be exerted to further develop the heterogeneous photocatalysis of this SrTiO3 under UV, visible, and solar illumination. Currently, unique and interesting features of binary photocatalyst system have gained more attention by researchers and it became a favourite research topic among various groups of scientists around the world. It was noticed that the binary photocatalyst system properties primarily depends on the nature of the surface properties, surface morphologies, as well as the role of optimum dopants amount incorporated into the SrTiO3. Thus, this article presents a critical review of recent achievements in the photocatalytic activity of the SrTiO3 for water splitting H2 generation technology. © 2019 Hydrogen Energy Publications LLC